Nurses' perceptions of dealing with death in the emergency department. Issue 1 (February 2021) - Gerace, Adam; Giles, Tracey; Breaden, Katrina; Hammad, Karen; Drummond, Christine; Bradley, Sandra L.; Muir-Cochrane, Eimear
ABSTRACT: Background: Providing end-of-life care to patients and their families in the emergency department (ED) is challenging, with high workloads, the busy environment, and a focus on providing lifesaving treatments to patients at odds with providing end-of-life and palliative care. Aim: The purpose of this study was to investigate nurses' experiences of providing end-of-life care in EDs, including their perceptions of the most vital elements of care, ability to provide aspects of care, as well as perceptions of their role, communication processes, family presence/involvement, and the ED environment. Methods: Nurses ( n = 211) working in Australian EDs for at least 12 months completed an anonymous online survey. Findings: Nurses identified vital elements of care for dying patients including adequate pain control and a move away from burdensome treatments, sensitive care of families and family access to loved ones, and a quiet environment. However, nurses were not always able to provide such care to their patients. Often, the ED was seen as an unsuitable place for end-of-life care or care of families once the patient had died, and communication between staff and between staff and families was challenging. Discussion: The ED physical environment, lack of staff training and debriefing, and lack of time to communicate with family, particularly after death, may compromise nurses' ability to provide end-of-life care that is satisfying to them, their patients, and families. Conclusion: There is a need for focus on the ED physical environment, staff training, and consideration of the emotional experiences of frontline nurses caring for patients at the end of life.